Genomics Approaches For Improving Salinity Stress Tolerance in Crop Plants - Chantre Nongpiur, Ramsong; Lata Singla-Pareek, Sneh; Pareek, Ashwani (Current Genomics, 2016)
Salinity is one of the major factors which reduces crop production worldwide. Plant responses to salinity are highly complex and involve a plethora of genes. Due to its multigenicity, it has been difficult to attain a complete understanding of how plants respond to salinity. Genomics has progressed tremendously over the past decade and has played a crucial role towards providing necessary knowledge for crop improvement. Through genomics, we have been able to identify and characterize the genes involved in salinity stress response, map out signaling pathways and ultimately utilize this information for improving the salinity tolerance of existing crops. The use of new tools, such as gene pyramiding, in genetic engineering and marker assisted breeding has tremendously enhanced our ability to generate stress tolerant crops. Genome editing technologies such as Zinc finger nucleases, TALENs and CRISPR/Cas9 also provide newer and faster avenues for plant biologists to generate precisely engineered crops.
Keywords: Crosstalk